SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA DENGAN METODE ALGORITMA FUZZY TSUKAMOTO DI SMP AL-ISLAM 1 SURAKARTA - Agung Wicaksono, Bebas Widada, Sri Hariyati Fitriasih (Jurnal Ilmiah SINUS, 2015)
Scholarships interpreted as a form of an award given to individuals in order to continue their education to a higher level. the provision of such financial assistance granted to individuals, college students or students who are used for the continuation of education reached by the scholarship program is expected to ease the burden of students in studying in particular the issue of costs. Tsukamoto fuzzy logic reasoning is one method that can be applied to construct a system as problem solving how to determine which eligible students in obtaining scholarships on the basis of interviews conducted by the authors to the organizing committee are as follows scholarship amount of income parents, the value of the interview conditions Economic family residence criteria, and the value - average semester. Based on the results of testing this application is very helpful team selectors scholarship reception in SMP Al-Islam 1 Surakarta because the calculation result of this application form and then through a total score ranking system will be known to the students who deserve a scholarship. Keywords: Scholarship, Fuzzy Tsukamoto, SMP Al-Islam 1 Surakarta.